Ginzburg–Landau turbulence in quasi‐CW Raman fiber lasers. Issue 6 (6th October 2015) - Sugavanam, Srikanth; Tarasov, Nikita; Wabnitz, Stefan; Churkin, Dmitry V.
Abstract : Fiber lasers operating via Raman gain or based on rare‐earth‐doped active fibers are widely used as sources of CW radiation. However, these lasers are only quasi‐CW: their intensity fluctuates strongly on short time scales. Here the framework of the complex Ginzburg–Landau equations, which are well known as an efficient model of mode‐locked fiber lasers, is applied for the description of quasi‐CW fiber lasers. Our results open debates about the common underlying physics of operation of very different laser types – quasi‐CW lasers and passively mode‐locked lasers. Abstract : Fiber lasers operating via Raman gain or based on rare‐earth‐doped active fibers are widely used as sources of CW radiation. However, these lasers are only quasi‐CW: their intensity fluctuates strongly on short time scales. Here the framework of the complex Ginzburg–Landau equations, which are well known as an efficient model of mode‐locked fiber lasers, is applied for the description of quasi‐CW fiber lasers. The vector Ginzburg–Landau model of a Raman fiber laser describes the experimentally observed turbulent‐like intensity dynamics, as well as polarization rogue waves. Our results open debates about the common underlying physics of operation of very different laser types – quasi‐CW lasers and passively mode‐locked lasers.